Tolerance in Islam - Indah Siti Saidah; Neng Hannah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss tolerance in Islam. The research method is a qualitative type through literature study by applying content analysis. The results and discussion of this study include the definition of tolerance, the meaning of Islam, and tolerance in Islam. This research concludes that Islam as a religion that is rahmatan lil 'alamin has regulated how the concept of tolerance itself, behaves properly, respects every difference, so as to create a state of peace. The recommendation of this research is a deeper study of tolerance in Islam from another perspective.